1992
DOI: 10.1093/ajcn/56.3.565
|View full text |Cite
|
Sign up to set email alerts
|

Estimated mineral intakes of toddlers: predicted prevalence of inadequacy in village populations in Egypt, Kenya, and Mexico

Abstract: Intakes of minerals and factors that might affect their bioavailability were estimated for 255 toddlers aged 18-30 mo living in villages in Egypt, Kenya, and Mexico. Mean intakes over 1 y were compared with international-requirement estimates by using a probability approach. The prevalence of iron intakes likely to be inadequate to prevent anemia was estimated as 35% in Egypt, 13% in Kenya, and 43% in Mexico. The prevalence of zinc intakes likely to be inadequate to meet basal requirements was estimated as 57%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 26 publications
1
107
0
1
Order By: Relevance
“…Comparison with Kenyan toddlers (Calloway et al, 1993;Murphy et al, 1992), who were, however, not breast-fed, showed that energy, protein, vitamin A, and iron intake was in a similar range, but fat intake was higher (50%) in our toddlers, whereas carbohydrate and calcium intake was higher (24 ± 41%) in the Kenyan children.…”
Section: Discussionmentioning
confidence: 60%
“…Comparison with Kenyan toddlers (Calloway et al, 1993;Murphy et al, 1992), who were, however, not breast-fed, showed that energy, protein, vitamin A, and iron intake was in a similar range, but fat intake was higher (50%) in our toddlers, whereas carbohydrate and calcium intake was higher (24 ± 41%) in the Kenyan children.…”
Section: Discussionmentioning
confidence: 60%
“…Percentage zinc bioavailability was then adjusted considering intake of animal protein as an enhancing factor (>16 g=4.18 MJ, þ5%) and calcium as an inhibiting factor (>500 mg=4.18 MJ, 75%; >750 mg=4.18 MJ, 710%). The algorithm used here was adapted from the guidelines put forth by FAO=WHO=IAEA (1996) for estimating zinc bioavailability based on diet type and was previously described by Murphy et al (1992).…”
Section: Determination Of Nutrient Intakes From Complementary Foodsmentioning
confidence: 99%
“…For non-haem iron, bioavailability was determined for each meal using an algorithm based on Monsen et al (1978) and modified by Murphy et al (1992). Starting with a basal percentage bioavailability of 5%, bioavailability was increased by the meal content of meat=fish=poultry protein (>9 g=4.18 MJ, þ5%; >27 g=4.18 MJ, þ10%) and ascorbic acid (>35 mg=4.18 MJ, þ5%; >105 mg=4.18 MJ, þ10%), and decreased by tannin-containing teas and coffees (250 g standard strength beverage, 720% of percentage bioavailability, to a maximum of 60% per meal).…”
Section: Determination Of Nutrient Intakes From Complementary Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from issues related to research design, the lack of consistency in these ®ndings may be attributed to the variability in the nutritional andaor health status of subjects across studies. IDA is often associated with other nutritional de®ciencies, particularly in poor populations of lowincome countries (Murphy et al, 1992). In such populations, iron therapy will generally remedy the IDA and replete iron stores.…”
Section: Introductionmentioning
confidence: 99%